Adiponectin Mediates the Protection of H2S Against Chronic Restraint Stress-Induced Cognitive Impairment via Attenuating Hippocampal Damage - Tang, Qiong-Yan; Li, Min; Chen, Lei; Jiang, Jia-Mei; Gao, Sheng-Lan; Xiao, Fan; Zou, Wei; Zhang, Ping; Chen, Yong-Jun (Frontiers in Behavioral Neuroscience, 2021)
Emerging evidence shows that chronic restraint stress (CRS) can induce cognitive dysfunction, which involves in hippocampal damage. Our recent research reveals that hydrogen sulfide (H2S), a novel gasotransmitter, protects against CRS-induced cognitive impairment, but the underlying mechanism remains unclear. Adiponectin, the most abundant plasma adipokine, has been shown to elicit neuroprotective property and attenutes cognitive impairment. Hence, the present work was aimed to explore whether adiponectin mediates the protective effect of H2S on CRS-induced cognitive impairment by inhibiting hippocampal damage. Results found that administration of Anti-Acrp30, a neutralizing antibody of adiponectin, obviously reverses sodium hydrosulfide (NaHS, an exogenous H2S donor)-induced the inhibition on CRS-induced cognitive impairment according to Y-maze test, Novel object recognition (NOR) test, and Morris water maze (MWM) test. In addition, Anti-Acrp30 blocked the protective effect of NaHS on hippocampal apoptosis in rats-subjected with CRS as evidenced by the increases in the amount of hippocampal TUNEL-positive neurons and the expression of hippocampal pro-apoptotic protein (Bax), and a decrease in the expression of hippocampal anti-apoptotic protein (Bcl-2). Furthermore, Anti-Acrp30 mitigated the inhibitory effect of NaHS on CRS-induced oxidative stress as illustrated by the up-regulation of malondialdehyde content and the down-regulation of superoxide dismutase activity and glutathione level in the hippocampus. Moreover, Anti-Acrp30 eliminated NaHS-resulted in the reduction of endoplasmic reticulum (ER) stress-related proteins including glucose-regulated protein 78, C/EBP homologous protein, and Cleaved Caspase-12 expressions in the hippocampus of rats-exposed to CRS. Taken together, these results indicated that adiponectin mediates the protection of H2S against CRS-induced cognitive impairment through ameliorating hippocampal damage.